Book of insects’ immune system: development and implementation with pbl in increasing students’ learning outcome - Dina Maulina; Median Agus Priadi; Dewi Lengkana; Tri Jalmo; Ave Suakanila Fauzisar; Mohamad Amin (Universitas Negeri Jakarta, 2020)
The purpose of this research was to develop a research-based reference book and applied it through the problem-based learning (PBL) using reference books in learning activities. The method for the reference book used the ADDIE development models. The reference book's effectiveness test results were conducted using a purposive sampling technique, with a total sample of 55 students and analyzed by t-test. The research results showed that the reference books of the development results were validated by media experts and material experts. The integration of the development of reference books in learning activities has an impact on increasing student understanding as demonstrated through the pre-test and post-test scores that differ significantly with t-value> t-table (4.149> 2.045) at p <0.05. Therefore, the development of the insect's immune system book with the PBL model increasthe student learning outcomes significantly. Also, this research has been able to improve students' ability and competence in solving problems in insects' immune system subject matter.